2014
DOI: 10.1186/1471-2334-14-420
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal infections in the intensive care unit: characteristics, treatment and determinants of outcome

Abstract: BackgroundAbdominal infections are frequent causes of sepsis and septic shock in the intensive care unit (ICU) and are associated with adverse outcomes. We analyzed the characteristics, treatments and outcome of ICU patients with abdominal infections using data extracted from a one-day point prevalence study, the Extended Prevalence of Infection in the ICU (EPIC) II.MethodsEPIC II included 13,796 adult patients from 1,265 ICUs in 75 countries. Infection was defined using the International Sepsis Forum criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 29 publications
2
86
0
3
Order By: Relevance
“…Отсутствие контроля источника и адекватной антибактериальной терапии является единственным модифицируемым фактором ри- Научный обзор / Scientific Review ска смертности у пациентов с внегоспитальными осложненными ИАИ, находящихся в ОИТ. Ор-ганная недостаточность ассоциирована с худшим прогнозом (1В) [42][43][44].…”
Section: научный обзор / Scientific Reviewunclassified
“…Отсутствие контроля источника и адекватной антибактериальной терапии является единственным модифицируемым фактором ри- Научный обзор / Scientific Review ска смертности у пациентов с внегоспитальными осложненными ИАИ, находящихся в ОИТ. Ор-ганная недостаточность ассоциирована с худшим прогнозом (1В) [42][43][44].…”
Section: научный обзор / Scientific Reviewunclassified
“…IAIs are the second cause of admission to the ICU in large series (16,17). The number of cases of peritonitis that required admission to an ICU due to organ failure had remained stable during time both community-acquired and nosocomial-related, however this latter group seems to be increasing in recent reports (18).…”
Section: Iaismentioning
confidence: 99%
“…In 2014, the EPIC II study [226], including 13,796 adult patients from 1265 ICUs in 75 countries, demonstrated ICU mortality was higher in patients with abdominal infections compared to those with other infections (29.4 vs. 24.4%, P < 0.001). In patients with septic shock, early appropriate empiric antimicrobial therapy has a significant impact on the outcome, independent of the site of infection [227].…”
Section: Statement 42mentioning
confidence: 99%